The Roland and Otuel romances and the Anglo-French Otinel - Melick, Elizabeth; Fein, Susanna, 1950-; Fein, Susanna, 1950-; Raybin, David B., 1951-; Raybin, David B., 1951- (Middle English texts (Kalamazoo, Mich.), 2019)
"This edition contains four Middle English Charlemagne romances from the Otuel cycle: Roland and Vernagu, Otuel a Knight, Otuel and Roland, and Duke Roland and Sir Otuel of Spain. A translation of the romances' source, the Anglo-French Otinel, is also included. The romances center on conflicts between Frankish Christians and various Saracen groups. In addition to Charlemagne and Roland, each romance features a Saracen character: either the kind but loathsome giant Vernagu or Otuel, Vernagu's handsome and sharp-tongued nephew. The romances deal with issues of racial and religious difference, conversion, and faith-based violence"--